Five decades of the Interamerican Journal of Psychology. A socio-bibliometric study - Polanco, Fernando; Beria, Josiane Sueli; Klappenbach, Hugo (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2018)
The Inter-American Journal of Psychology (RIP) is the scientific publication of the Inter-American Psychological Society and one of the most influential and well established journals in the Americas. We realized a socio-bibliometric analysis based on the first 50 volumes of the publication (1967-2016). This methodology is part of the ex post facto studies pertaining to the history of psychology. It was observed that the general structure of the RIP was characterized by the diversity and frequent changes of its staff and its advisory and scientific boards. Considering the language, it is highlighted that papers were published in Spanish, English and Portuguese. The three most productive authors were R. Ardila, R. Díaz-Loving, and L. F. Natalicio. The analysis of citations showed the great concentration of references to North-American papers and books; publications devoted to locus of control, social learning and transcultural, social and community psychology the most frequently referenced. The conceptual analysis showed that the roots of the production of the RIP sink into the concepts of behavior and cognition, analyzed from experimental and psychometric methods mainly based on North-American social psychology. Childhood is the main population analyzed, and the applied fields preferred were clinical, social, cultural and educational. In conclusion, it is observed that the intellectual origin reflected in the RIP is strongly biased by the general features of the North-American psychology, with emphasis on experimental, differential, social and applied psychology.